1974
DOI: 10.1063/1.1663555
|View full text |Cite
|
Sign up to set email alerts
|

Light scattering from boron trioxide through the glass transition

Abstract: Light scattering from boron trioxide has been studied as a function of temperature in the melt near the glass transformation temperature and in the solid. Both polarized and depolarized spectra were obtained. At all temperatures (20–516°C) the scattering consists of a polarized contribution associated with density fluctuations and a depolarized component presumably connected with the anisotropic nature of the B2O3 glass network. Quantitative results are presented confirming that the polarized scattering from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…where I RS VH and I RS VV are Rayleigh scattering intensities measured at parallel and perpendicular polarizations, and relationship for 90°scattering [19]:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…where I RS VH and I RS VV are Rayleigh scattering intensities measured at parallel and perpendicular polarizations, and relationship for 90°scattering [19]:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…46 Subsequent work showed that ''dry'' v-B 2 O 3 is also a strong light scatterer when compared to other glasses. 47 The polarized light scattering is due to density fluctuations while the depolarized scattering is due to low symmetry of network-forming units. It is the anisotropy of planar BO 3 and B 3 O 6 groups ͑as compared to tetrahedral BO 4 Ϫ and SiO 4 groups͒ which makes v-B 2 O 3 to scatter light Ϸ10 times stronger than other oxide glasses.…”
Section: A the Structure Of V-b 2 O 3 :Ohmentioning
confidence: 99%
“…These fluctuations are responsible for optical scattering [1][2][3] and are a major contributor to spatially heterogeneous dynamics in glass and glass-forming liquids [4][5][6][7]. The magnitude of density fluctuations is known to be dependent on the thermal history of the glass [6,[8][9][10][11] as quantified through its fictive temperature [12].…”
Section: Introductionmentioning
confidence: 99%